PENGARUH PENINGKATAN KUALITAS SERAT RESAM TERHADAP KEKUATAN TARIK, FLEXURE DAN IMPACT PADA MATRIKS POLYESTER SEBAGAI BAHAN PEMBUATAN DASHBOARD MOBIL - Herwandi Wandi (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2015)
Resam plant (Dicranopteris linearis) is a forest fern living in rubber plantations and can be found in almost all provinces of  indonesia. The plant spreads and has a length of about 7 meters. Research concerning resam fiber for composite material had been done by the author until the end of  2014. Studies by other researchers showed that the use of natural fibers as a composite material could be improved by NaOH. This is very useful to improve the quality of the resam fiber research. The purpose of this study was to obtain new composite materials, the result of a chemical treatment with NaOH to resam fiber. The stages of the research process consist of making test samples, mechanical testing and data analysis. The materials for making the samples comprise of fiber, resin Yukalac 157 BQTN-EX, MEKPO as  a hardener, 5 % NaOH and Wax glasses as a preventive attachment of resin into the mold. The test sample was made by mixing random fibers into the resin. Previous fibers  were already made of three length: 20 mm, 40 mm and 60 mm. Then the fiber was weighed according to the percentage desired. Fiber percentage was 25%, 30% and 35%. The curing agent was 1,5%. The size of  the test sample was based on standard tensile test (ASTM D 638), flexure test (ASTM D 790) and the impact test (ISO 179). The highest value of tensile was 30,750 MPa, elastic modulus was 9400 MPa and a strain 0,315%. The maximum value of  the flexure strain was 138 MPa and a flexural modulus was 4880 MPa, while the highest value of  impact was 54,14 kJ/m2.  Based on the findings, it can be concluded that the results of tensile test, flexure test and impact test already meet the standard plastic used for car dashboard.